APLIKASI MEDIA PEMBELAJARAN INTERAKTIF MATEMATIKA: Math, Learning Media, Adobe flash cs3 - Lestari, Ayu; -, Afrizal (JURNAL AKADEMIKA, 2017)
Mathematics is a subject that is considered difficult for most students. This is because mathematics demands to think hard and tend to be abstract so that students find it difficult to understand it. The basic concept of mathematics is a matter of principle and important to support the development of further learning outcomes, one of which is the matter of ordinary fractional operations. Some elementary school students consider ordinary fractional operations are a difficult subject. In SDN 204 / IV Kotabaru Jambi, a lesson learned especially in Mathematics lesson. With the sophistication of technology, the authors use computer media as a medium they like, by making an apilkasi adobe-based learning media flash cs3.Penelitian aims to build an application of mathematical learning media operations of traditional fractions and apply Adobe Flash CS3 Professional in order to improve interest in learning of the students as well as improving the quality and quality of elementary school students 204 / IV Kotabaru Jambi.